IMPLEMENTATION OF PEARLS ANALYSIS TO MEASURE THE FINANCIAL PERFORMANCE OF COOPERATIVES - Wahyu Maulana; Very Andrianingsih (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2021)
This study aims to determine the financial performance of cooperatives using PEARLS analysis. The data sources used are secondary data sources in the form of financial reports from 2017 to 2019 and non-financial reports in the form of data on the number of members. The results showed that the cooperative's financial performance on variable P showed a non-ideal performance; variable E shows indicators E1 and E5 are not ideal, E6 is less than ideal and E9 is ideal; variable A shows non-ideal performance; Variable R shows indicators R9 is not ideal and R12 is ideal; variable L indicates the category is not ideal; and the S variable shows that S10 is not ideal and S11 is less than ideal. From the analysis of PEARLS indicate that the performance of cooperatives in a state which is not good because of the 13 indicators studied, only three indicators that show the ideal categories while the 8 indicators are always in a state which is not ideal and the two other indicators simply ideal in a given year